Exploring Race and Income Heterogeneity in the Effects of State Merit Aid Loss Among Four-Year College Entrants. (19th September 2022) - Cummings, Kristen M.; Deane, KC; McCall, Brian P.; DesJardins, Stephen L.
ABSTRACT: Despite the robust literature on the effects of financial aid, the effects of financial aid loss remain largely understudied. We employ a regression discontinuity design, leveraging a minimum GPA scholarship renewal threshold, to examine the effect of losing state merit aid eligibility on college student stop-out, transfer, and bachelor's degree completion. We estimate the effects of GPA-based eligibility loss for low- and higher-income students, Black and White students, and the interactions of the two separately. Using longitudinal state administrative data from academic years 2011 to 2014 on four cohorts of students attending public four-year colleges, we find evidence that the effects of eligibility loss at the first renewal checkpoint differ among the subgroups of interest. Losing eligibility for a state merit aid scholarship at the first renewal checkpoint leads to increased stop-out among higher-income White students and increased transfer to a community college among low-income Black students. State merit aid loss has no statistically significant effect on on-time bachelor's degree completion but causes a decrease in the probability of 150% time bachelor's degree completion for Black students. We close with implications for policy and research.